2021
DOI: 10.1096/fj.202100991r
|View full text |Cite
|
Sign up to set email alerts
|

Choline acts during preimplantation development of the bovine embryo to program postnatal growth and alter muscle DNA methylation

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 59 publications
0
7
0
2
Order By: Relevance
“…A significant change in the glycerophospholipid metabolism pathway was also identified in thigh muscle, which was screened in breast muscle, which may perform similar functions in thigh muscle. Michel et al reported that food supplemented with choline improved the birth weight of cattle by lowering DNA methylation [ 66 ]. The concentration of choline decreased significantly in both breast and thigh muscles in line S chickens ( Figure 4 ), which suggested that selection accelerated the consumption of choline and promoted muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…A significant change in the glycerophospholipid metabolism pathway was also identified in thigh muscle, which was screened in breast muscle, which may perform similar functions in thigh muscle. Michel et al reported that food supplemented with choline improved the birth weight of cattle by lowering DNA methylation [ 66 ]. The concentration of choline decreased significantly in both breast and thigh muscles in line S chickens ( Figure 4 ), which suggested that selection accelerated the consumption of choline and promoted muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies reported that the maternal diet during gestation affects the DNA methylation pattern in the placenta and offspring of mice (Ge et al, 2014;Mahajan et al, 2019;Zhang et al, 2021a), cattle (Liu et al, 2021), and humans (Daniels et al, 2020;Kupers et al, 2022). Interestingly, a study showed that the exposure of IVP embryos to choline in the culture medium alters the DNA methylation profile in the offspring muscle (Estrada-Cortes et al, 2021). However, these studies evaluated the effects during embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Holstein heifers derived from embryos treated with CSF2 from day 5 to day 7 of development had similar birth weights as heifers derived from control embryos but experienced accelerated body growth after 3 months of age ( Kannampuzha-Francis et al, 2015 ). In another experiment ( Estrada-Cortés et al, 2021a ), addition of the methyl donor choline to culture medium of IVP embryos resulted in an increase in birth and weaning weight in Brahman cattle ( Fig. 5 ).…”
Section: Optimizing Postnatal Phenotypementioning
confidence: 94%
“…Transfer of the IVP embryo can also improve fertility in certain situations such as during heat stress and for the repeat-breeder cow and, as discussed by Hansen (2020a) , improvements in the technologies associated with embryo production could result in fertility enhancement more broadly. Furthermore, the preimplantation embryo is amenable to developmental programming; culture media can be modified to produce offspring with phenotypes desirable for production ( Estrada-Cortés et al, 2021a ; 2021b ).…”
Section: Toward the Goal Of An In Vitro -Produced ...mentioning
confidence: 99%
See 1 more Smart Citation